PENGARUH TERPAAN KONTEN TASYA FARASYA TERHADAP MINAT BELI LUXURY BRAND PADA PERIODE OKTOBER-DESEMBER 2023 - Ananda, Pianica; Santoso, Budi (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
Social media has evolved into an important platform for influencers to promote various products, including those from luxury brands. Influencers such as Tasya Farasya, who has a large following on Instagram, play a big role in influencing consumer behavior, including purchase intention towards luxury products. This study aims to analyze the effect of Tasya Farasya's content exposure on the purchase intention of luxury brands on her Instagram followers in the period October to December 2023. This research uses a quantitative approach with data collection techniques through online questionnaires distributed to 100 respondents selected by purposive sampling. The variables studied include content exposure (frequency, duration, and attention) as the independent variable, and purchase intention as the dependent variable. The data obtained were then analyzed using linear regression. The results showed that Tasya Farasya's content exposure did not have a significant influence on the purchase intention of luxury brands, with a contribution of only 6.3%. The more dominant factors in influencing purchase intention are external factors such as price, product quality, and personal motivation, which together contribute 93.7%. The conclusion of this study is that although exposure to influencer content has a slight contribution to purchase intention, external factors are more decisive in the purchase decision of luxury products. The findings provide insights for marketers on the importance of considering other factors beyond influencer content in designing luxury product marketing strategies